The Dark Side of Organizational Identification: A Multi-Study Investigation of Negative Outcomes - Irshad, Muhammad; Bashir, Sajid (Frontiers in Psychology, 2020)
After more than two decades of research on the positive side of organizational identification, researchers have begun to realize that it also has a dark side that needs immediate consideration. With support from social identity theory, the current study sheds light on the understudied role of the dark side of organizational identification by investigating its indirect effects on (a) psychological entitlement, (b) unethical pro-organizational behavior, and (c) pro-social rule-breaking through externally motivated organizational citizenship behavior, taking leader–member exchange as a boundary condition. Two surveys were conducted to test the proposed moderated mediation model. Data for the study 1 was collected from employees (N = 356) working in the service sector (i.e., Universities, Banks and Telecommunication Organizations), whereas responses for study 2 were taken from employees (N = 259) working in the hospitality industry. A time-lagged research design was selected for both surveys to avoid common method bias. The results demonstrate that organizational identification leads to adverse outcomes in the form of psychological entitlement, pro-social rule-breaking and unethical pro-organizational behavior through externally motivated organizational citizenship behavior. Furthermore, a high-quality leader–member exchange relationship enhances these indirect effects of organizational identification. Several theoretical and practical implications, along with limitations and future research directions, are also discussed.